The impact of internet usage on the mental health of older adults in China: empirical analysis from a multi-dimensional perspective - Lu, Wanjun (Frontiers in Public Health, 2024)
The process of population aging in China is currently undergoing rapid acceleration. Simultaneously, the swift advancement of digitalization is fundamentally transforming individuals' lifestyles. The usage of the internet and mobile internet tools by the elderly population is relatively inadequate. The issue of digital exclusion and its impact on the life quality of the elderly population has received significant attention.Objective: This study utilized microdata from the China Health and Retirement Longitudinal Study (CHARLS 2020) to empirically investigate the impact of internet usage on the mental health of elderly individuals. The depression index was utilized to assess the mental health, while four variables were employed to evaluate internet usage among the elderly in this study.The Center for Epidemiological Studies Depression Scale (CES-D) in CHARLS data was used to measure the depression index of the elderly. Four variables including usage of internet, usage of WeChat, usage of WeChat moments and usage of mobile payment were used to represent the internet use of the elderly, and there was progressive relationship between these four variables. In the empirical study, multiple regression analysis was adopted to empirically analysis the impact of internet usage on the mental health of the elderly. In order to reduce the influence of endogenous problems on regression results, the propensity score matching method was used to verify the validity and robustness of regression results.(1) Internet usage can significantly reduce the psychological depression of the elderly and promote the formation of positive psychology; (2) With the increase of the depth of internet usage, especially the use of mobile internet and mobile payment, the internet use will have greater improvement effect on the depression; (3) The heterogeneity test found that there were certain differences in the impact of internet usage on different elderly groups; (4) Through a step-by-step analysis of 10 sub-indicators of depression index, the study found that Internet use mainly affected four indicators: "life hope", "happiness", "loneliness" and "life confidence", while demonstrating no significant effect on other sub-indicators.According to the research, internet usage can significantly reduce the psychological depression index of the elderly and promote the formation of positive psychology.